2005
DOI: 10.12968/ijpn.2005.11.10.19983
|View full text |Cite
|
Sign up to set email alerts
|

What influences decisions around the place of care for terminally ill cancer patients?

Abstract: For many, the preference for place of care at the end of life was conditional on how the process of their disease advanced. It was not a clear and positive choice, but it did include the desire to be cared for in a place other than home. Carer availability and ability were influencing factors; however, decisions reflected the patient's perceptions of resources rather than those of the carer, even when the carer was available and able. The challenge to those who work with the terminally ill is to develop effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 12 publications
1
66
0
1
Order By: Relevance
“…Previous qualitative studies have reported that health care professionals often do not involve patients in important treatment decisions. 24 Some patients may not want an active role and are more than willing to let their doctors select their care providers. 25,26 Other patients may be too overwhelmed, especially when given the cancer diagnosis, to process all the information and ask questions about the referral process.…”
Section: Discussionmentioning
confidence: 99%
“…Previous qualitative studies have reported that health care professionals often do not involve patients in important treatment decisions. 24 Some patients may not want an active role and are more than willing to let their doctors select their care providers. 25,26 Other patients may be too overwhelmed, especially when given the cancer diagnosis, to process all the information and ask questions about the referral process.…”
Section: Discussionmentioning
confidence: 99%
“…6,22,43,50,51,[67][68][69][70][71][72][73] Running like a leitmotif throughout the literature is that patients strongly desire not to impose a burden of care on their family members 5,22,69,[73][74][75][76][77][78][79] and it is evident that most people depend on the availability and willingness of informal carers to support their ability to die at home. 69,73,80 As the population ages, increasing numbers of the very old live alone and may not have carers available to help. However, dying alone is generally regarded as a very bad outcome, and for most patients it is not an acceptable option.…”
Section: Preferred Place Of Deathmentioning
confidence: 99%
“…22,59,66,69,142,180 The focus on place has deflected attention from how death is experienced in different settings. 69,72,73,77,179 Patients tend to adopt a pragmatic stance to place of death. Home might be preferred in principle, but that preference over-ridden by contextual factors, 67,69 and hospital is not necessarily dispreferred.…”
Section: 132139mentioning
confidence: 99%
See 2 more Smart Citations